Organic Nanofibers: Extending the Lasing Wavelength Coverage of Organic Semiconductor Nanofibers by Periodic Organic–Organic Heteroepitaxy (Advanced Optical Materials 2/2013). Issue 2 (22nd February 2013) - Quochi, Francesco; Schwabegger, Günther; Simbrunner, Clemens; Floris, Francesco; Saba, Michele; Mura, Andrea; Sitter, Helmut; Bongiovanni, Giovanni
<x xml:space="preserve">Abstract</x> Thin films of organic epitaxial nanofibers represent a viable strategy towards the realization of effective organic semiconductor lasers. Outlined on page 117, a novel approach based on organic‐organic heteroepitaxy is taken by F. Quochi et al. to endow the nanofibers with a highly functional oligomer heterostructure, enabling random lasing with low thresholds in multiple bands across the visible spectrum. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>